PENGKAJIAN USAHATANI BAWANG MERAH DI KABUPATEN CIREBON - Yati Haryati; Agus Nurawan (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
Assessment on Shallot Farm Operations in Cirebon Regency. Shallot is the most important commodity that can be relied on as it contributes most to the farmer household income and agricultural development in Playangan Village. The assessment was conducted in Playangan village, Gebang Sub district, Cirebon Regency from May to June 2008 in the land owned by farmers. The assessment method used two comparable treatments namely the implementation of recommended farm operation system (cooperator farmers) and the not n suggested one (non cooperator farmers). Each treatment was replicated for 20 cooperator farmers in the same group. The land area covered 10 hectares. The assessment was carried out by performing preliminary survey covering the characterization of and the implementation of the fertilizing technology package recommendation, i.e. the use of 200kg/ha Urea, 200 kg/ha SP-36, 200 kg/ha ZA and 100 kg/ha KCl and the control of shallot pest using sex pheromone. The data analysis was performed on the shallot agronomy, the intensity of shallot pest (Spodoptera exigua) attacks and the farm operation income using t-test, B/C and descriptive statistics. The results show that the implementation of recommended technology used by cooperator farmers reached 20 t/ha with B/C 2.08, while that of non cooperator farmers was 18 t/ha with B/C 1.50.Key words : Shallot, farming, technology adoptionABSTRAKBawang merah merupakan komoditas terpenting yang dapat diandalkan, karena sebagai kontribusi terbesar dalam pendapatan rumah tangga petani maupun pembangunan pertanian di Desa Playangan. Pengkajian dilaksanakan di Desa Playangan, Kecamatan Gebang, Kabupaten Cirebon pada Bulan Juni sampai dengan Agustus 2008 pada lahan milik petani. Metode pengkajian menggunakan 2 perlakuan yang dibandingkan yaitu penerapan sistem usahatani anjuran (petani koperator) dan non anjuran (petani non koperator). Masing-masing perlakuan diulang pada 20 petani koperator dalam kelompok yang sama. Luas lahan mencakup 10 ha. Pengkajian dilakukan dengan diawali survey pendahuluan meliputi karakterisasi dan penerapan paket teknologi pemupukan sesuai rekomendasi Urea 200 kg/ha, SP-36 200 kg/ha, ZA 200 kg/ha dan KCl 100 kg/ha serta pengendalian hama ulat bawang dengan menggunakan feromon seks. Analisis data dilakukan terhadap keragaan agronomis bawang merah, intensitas serangan hama ulat bawang (Spodoptera exigua) dan pendapatan usahatani dengan menggunakan uji t, B/C dan statistik deskriptif. Hasil pengkajian menunjukkan bahwa penerapan teknologi anjuran yang digunakan petani koperator mencapai 20 t/ha dengan B/C 2,08 dan petani non koperator 18 t/ha dengan B/C 1,50.Kata kunci : Bawang merah, usahatani, adopsi teknologi